PROTOTYPE APLIKASI RECORDING TERNAK TERINTEGRASI DENGAN SISTEM IDENTIFIKASI DAN SERTIFIKASI TERNAK DI KABUPATEN KEBUMEN - Untung Subagyo (LPPM STMIK El Rahma Yogyakarta, 2019)
The Government of the Department of Agriculture and Food / Dinas Pertanian dan Pangan (Distapang) of Kebumen Regency has utilized information technology to register livestock and provide identity cards to livestock with the Livestock Card Database System. With this system, Distapang Kebumen can quickly find out the livestock population and household of farmers. Kebumen Regency is one of the best cattle breeding areas at the national level, namely for PO cattle. Therefore, the Agriculture and Food Service Office of Kebumen Regency provides a Breeding Certificate /Surat Keterangan Layak Bibit (SKLB) for livestock. SKLB will increase trust and satisfaction of livestock breed users, and will certainly increase the price of livestock. To make SKLB, Distapang uses the help of the SKLB Recording and Printing System ... Unfortunately, between the Livestock Card Database System and the SKLB Recording and Printing System is not integrated, so there is one job carried out by two officers, namely livestock data collection. Data on making livestock cards comes from forms filled out by data officers in the village area from livestock, while data recording comes from recording officers from members of the herd group / designated officers. The output of this research is in the form of an Android-based recording application prototype design, which is integrated with the Livestock Card Database System as an Identification System, and the SKLB Recording and Printing System as a System for Animal Certification